Untangling the taxonomy of Phlogacanthus pulcherrimus (Acanthaceae) newly recorded from Vietnam - Hai, Do Van; Hoan, Duong Thi; Nuraliev, Maxim S.; Kuznetsov, Andrey N.; Kuznetsova, Svetlana P.; Choudhary, Ritesh Kumar; Lee, Joongku (Phytotaxa, 2021)
The present work is an effort to untangle the taxonomy of Phlogacanthus pulcherrimus, a poorly known species reported here for the first time for the flora of Vietnam. Fresh specimens of this species were collected from three localities in Southern Vietnam. They provided new insights to its appearance and morphology. Phlogacanthus pulcherrimus can be distinguished from the morphologically close P. geoffrayi and P. turgidus by oblanceolate-obovate, light to dark purple flower-subtending bracts, oblanceolate bracteoles, and staminodes 1 mm long. The corolla of the Vietnamese specimens of P. pulcherrimus is uniformly dark purple outside. A detailed description, photographs, and information on habitat, ecology and distribution of P. pulcherrimus are provided. Typification of this name is performed, and a specimen at K (K000885620) is designated as a lectotype.